AB0870 Thirteen-year clinical follow-up of spondyloartrhitis patients: data from the regisponser database. (12th June 2018) - Pérez Sánchez, L.; López, C.; Font, P.; Bautista, L.; Ladehesa, M.L.; Gómez, I.; Escudero, A.; Collantes, E.; Castro, M.C.
Abstract : Objectives: To describe the clinical characteristics of the SpA patients included in the REGISPONSER database during 13 years of follow-up, regarding the evolution of the clinical manifestations and the treatment used. Methods: An observational and analytical study of a retrospective cohort was carried out, in which 78 patients were analysed at the Reina Sofía University Hospital of Córdoba for the first time in the year 2004/05. The last visit registered was reviewed during the years 2016/17. Data about his clinical condition, including extra-axial manifestations, and treatment was collected. Results: Seventeen out of 78 SpA patients included in the registry were lost. The characteristics of this cohort are shown in table 1. Recurrence of uveitis was observed in 10 out of 14 (71.4%) patients (p<0.001), with a low recurrence at the end of the follow-up (5%). At the time of inclusion, uveitis was not present in 45 SpA patients, however was present in 8 of them (17.8%) during wollow-up. Three out of the 15 patients who had history of lower limbs peripheral arthritis in the first registry, presented new flares at the end of the study, showing a low level of recurrence (3%). During follow-up, enthesitis was present in 8 out of 45 SpA patients (17.8%) who didn't have a previous history of enthesitis. In adittion, only one episode of dactilitis was detected from the 55 SpA patients who didn't have a previous history of dactilitis. The last CRP value was mean of 5.90 (8.13) mg/dl. Besides, three patients required placement of a hip prosthesis during follow-up. At last visit, we found a response to NSAIDs in 54 patients (88.5%), 33 of them (61.1%) with daily treatment. Biological therapy was present in 25% of the patients, 15 showing a mean time of 18.8 (7.4) years from the appearance of the first symptoms until their indication. A good response was achieved in 50% of patients with the first biologic indicated. Loss of efficacy was the most frecuent cause (62%) of therapy change. Currently golimumab and etanercept are the most commonly used, prescribed in 5 (33%) and 4 (26%) patients respectively. Conclusions: The results obtained suggest that the follow-up of a cohort of patients with spondyloarthritis in a specialised monographic medical centre allows a control of the symptoms, with a low recurrence of extra-axial manifestations. We can conclude from this study that most patients with spondyloarthritis (75%) could have good control of their disease with NSAIDs in the long term. Disclosure of Interest: None declared